The genetic basis of phage susceptibility, cross-resistance and host-range in Salmonella. Issue 12 (15th December 2021) - Adler, Benjamin A.; Kazakov, Alexey E.; Zhong, Crystal; Liu, Hualan; Kutter, Elizabeth; Lui, Lauren M.; Nielsen, Torben N.; Carion, Heloise; Deutschbauer, Adam M.; Mutalik, Vivek K.; Arkin, Adam P.
Abstract : Though bacteriophages (phages) are known to play a crucial role in bacterial fitness and virulence, our knowledge about the genetic basis of their interaction, cross-resistance and host-range is sparse. Here, we employed genome-wide screens in Salmonella enterica serovar Typhimurium to discover host determinants involved in resistance to eleven diverse lytic phages including four new phages isolated from a therapeutic phage cocktail. We uncovered 301 diverse host factors essential in phage infection, many of which are shared between multiple phages demonstrating potential cross-resistance mechanisms. We validate many of these novel findings and uncover the intricate interplay between RpoS, the virulence-associated general stress response sigma factor and RpoN, the nitrogen starvation sigma factor in phage cross-resistance. Finally, the infectivity pattern of eleven phages across a panel of 23 genome sequenced Salmonella strains indicates that additional constraints and interactions beyond the host factors uncovered here define the phage host range.